Analisis Spasial Kasus Diabetes Melitus dan Faktor Risiko di Provinsi Sumatera Utara Tahun 2023: Penelitian - Rista Riviani; Erna Mutiara; Heru Santosa; Arifa Masyitah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels, potentially damaging organs such as blood vessels, kidneys, heart, and nerves. Indonesia ranks fifth globally in diabetes prevalence, with 19.5 million cases. According to the 2023 Indonesia Health Survey (SKI), the national prevalence among individuals aged ≥15 is 2.2%, and 1.9% in North Sumatra. Despite extensive research on risk factors, spatial analysis remains limited. This study aims to map the spatial distribution of diabetes cases and associated risk factors in North Sumatra in 2023. A descriptive quantitative method using Geographic Information Systems (GIS) and spatial analysis was applied to 39,919 SKI 2023 records. Results identified Medan (28.20%), Deli Serdang (12.97%), and Langkat (8.11%) as areas with very high case rates. Risk factors spatially aligned with case distribution include smoking and physical inactivity. Local governments are encouraged to design area-based interventions targeting modifiable risk factors and strengthen focused diabetes prevention strategies.